ANALISIS TOKO NEW PELITA MOTOR DALAM PENGELOLAAN PERMINTAAN DAN KAPASITAS PRODUKSI DI KOTA BATAM - Fiona; Novi Aprillia; Kelly; Jesslyn Clorina; Fitriana Aidnilla Sinambela (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
The economic crisis that has occurred around the world since the emergence of the Covid-19 pandemic has had a severe impact on the operational costs of a business. With that, the purpose of this research is to assist the New Pelita Motor Store in dissecting the problems that exist in them, especially in managing demand and production capacity. Data collection techniques used are literature studies and interviews with owners and employees at the New Pelita Motor Store. The interview questions discussed how their day-to-day operations were, as well as how their sales progressed from period to period. The results obtained are that the management of demand and capacity of these partners has not been effective in the operation, because New Pelita Motor Store tends to be in a manual or traditional operational position. Therefore, suggestions that can be given are to improve the consumer experience when and after receiving services and balance their demands through promotional media to get optimal production capacity.